IMPROVEMENT OF STUDENTS LEARNING OUTCOMES AND RESPONSE THROUGH THE UTILIZATION OF NATURAL LABORATORY - Fera Annisa; Ega Januarina (Lantanida Journal, 2019)
Experiments/practical activities in science learning are important, but it cannot be denied that there are limitations in infrastructure facilities in the implementation of the practicum. To overcome this, one solution is to empower natural laboratories. Natural laboratories, namely the whole world around us, both original and man-made, are often overlooked for practical activities. In addition, students will be very interested if science lesson observations make use of the natural rides around. The purpose of this study was to determine the learning outcomes and responses of students with the use of natural laboratories as student learning facilities in MIN Sabang. The research design used was pre-experiment with a population of all IV classes of MIN Sabang, while for the sample in this study were IV1 students 22 students are also called Total Sampling. Data collection techniques in this study were tests and student response questionnaires. Based on the results of the study obtained student learning outcomes can be increased from the pre-test value of 31.82 to 76.14 post-test values. The results of hypothesis testing with t-test statistics were obtained by t count t table or 18.62-1.72 so that Ha was accepted, student learning response data had an increase of 89.9% which was very good criteria. Then it can be concluded that the use of natural laboratories can improve learning outcomes and responses in material changes in the form of objects in MIN Sabang.